Sexual assault: the victims, the perpetrators, and the criminal justice system - Reddington, Frances P.; Kreisel, Betsy Wright (Carolina Academic Press, 2017)
"[This book provides an] overview of the crime of sexual assault by adding new chapters on drug facilitated sexual assault, child sexual abuse, sexual abuse of the elderly, sex offender treatment and public policy concerning sex offenders. In addition, the second edition [of this title] provides more special features which truly complement the academic sections of the book. Also, this new edition completes each of the six parts of the text with a page of suggested discussion questions, videos to show and class activities. [The authors] approach the topic of sexual assault in a unique way by examining it from a criminal justice perspective."--